2016
DOI: 10.1177/1077801216647796
|View full text |Cite
|
Sign up to set email alerts
|

Family Violence in Domestic Homicides

Abstract: This article examines the impact of legislative reforms enacted in 2005 in Victoria, Australia, on legal responses to women charged with murder for killing their intimate partner. The reforms provided for a broader understanding of the context of family violence to be considered in such cases, but we found little evidence of this in practice. This is partly attributable to persistent misconceptions among the legal profession about family violence and why women may believe it necessary to kill a partner. We rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…As such, while self-defense is universally acknowledged to be the preferable defense for those who kill in response to prolonged abuse, abused women are not generally successful in raising self-defense, particularly those who kill in non-traditional self-defense scenarios (Sheehy et al, 2012a;Tarrant, 2018;Tyson et al, 2017). In their review of homicide cases involving abused women from 2000 to 2010 in Australia, Canada and New Zealand, Sheehy et al (2012a) found that of the 67 Australia cases identified, only 11 (16%) involved women being acquitted on the basis of self-defense, with only three of these cases involving non-confrontational circumstances when the threat of harm was not imminent.…”
Section: Legal Barriers For Women Who Kill An Abusive Partnermentioning
confidence: 99%
See 2 more Smart Citations
“…As such, while self-defense is universally acknowledged to be the preferable defense for those who kill in response to prolonged abuse, abused women are not generally successful in raising self-defense, particularly those who kill in non-traditional self-defense scenarios (Sheehy et al, 2012a;Tarrant, 2018;Tyson et al, 2017). In their review of homicide cases involving abused women from 2000 to 2010 in Australia, Canada and New Zealand, Sheehy et al (2012a) found that of the 67 Australia cases identified, only 11 (16%) involved women being acquitted on the basis of self-defense, with only three of these cases involving non-confrontational circumstances when the threat of harm was not imminent.…”
Section: Legal Barriers For Women Who Kill An Abusive Partnermentioning
confidence: 99%
“…Abused women are also hindered by misconceptions and inaccurate understandings of the nature and dynamics of domestic abuse, with women often asked why they did not just leave the relationship (Douglas et al, 2020;Hopkins et al, 2018;Mechanic, 2023;Tarrant et al, 2019;Tyson et al, 2017). While expert evidence on battered woman syndrome (BWS) was originally introduced as a defense strategy in Australia, Canada, and the United States to help explain why a woman's resort to lethal violence may have been reasonable in the context of abuse, it has been extensively criticized for portraying their actions as the result of an individual deficit or pathology rather than a rational and reasonable response to serious domestic violence (Bradfield, 2002;Schneider, 2000;Stubbs & Tolmie, 1999).…”
Section: Legal Barriers For Women Who Kill An Abusive Partnermentioning
confidence: 99%
See 1 more Smart Citation
“…It was abolished in 2014 because it was seen as being too readily used by men charged with killing other men. A number of feminist researchers and advocates were critical of the proposal to abolish defensive homicide, arguing that it provided an important alternative for women who were able to show that they genuinely believed they faced lethal violence but where the jury was not satisfied that the belief or response was reasonable (DVRCV, Monash University et al 2013;Tyson et al 2016).…”
Section: Abolition Of Defensive Homicidementioning
confidence: 99%
“…We should also stress that our aim in this article is to investigate the application of the provocation reforms to men who kill. We do not discuss their application to women who kill abusive partners, which raises different issues and has been the subject of separate research (see Kirkwood et al, 2013;Tyson et al, 2015Tyson et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%